Impacts of Parliamentary Debate on Speaking Skills: An Extracurricular Case Study - Adivta Yudha Tama; Ashadi; Yuyun Yulia (Universitas Sarjanawiyata Tamansiswa, 2026)
Debate activities have been widely recognized as a potential medium for developing students’ speaking skills in higher education contexts. However, empirical studies that explore how debate activities function as a learning space, particularly within extracurricular activities like English Debating Societies (EDS), remain limited. This study aims to investigate the impacts of participation in debate activities on EDS members’ speaking skills. This study employed a qualitative case study design conducted in an English Debating Society at Universitas Negeri Yogyakarta. Data were collected through classroom observations and semi-structured interviews. The research instruments included observation checklists and interview guides. The collected data were analyzed using thematic analysis. The findings indicates that participation in debate activities contributes meaningfully to the development of both micro and macro speaking skills, including fluency, grammatical accuracy, lexical precision, coherence, and strategic speech delivery. The study recommends that debate activities be strategically supported within both extracurricular and instructional contexts to maximize their effectiveness in fostering the development of English-speaking skills.